A Pilot Study on Bioactive Constituents and Analgesic Effects of MyrLiq®, a Commiphora myrrha Extract with a High Furanodiene Content. (24th May 2017) - Germano, Antonio; Occhipinti, Andrea; Barbero, Francesca; Maffei, Massimo E.
Abstract : The analgesic properties of myrrh (Commiphora myrrha) have been known since ancient times and depend on the presence of bioactive sesquiterpenes with furanodiene skeletons. MyrLiq is a C. myrrha extract with a standardized content of curzerene, furanoeudesma-1, 3-diene, and lindestrene (12.31 ± 0.05 g kg −1, 18.84 ± 0.02 g kg −1, and 6.23 ± 0.01 g kg −1, resp.) and a high total furanodiene content (40.86 ± 0.78 g kg −1 ). A balanced sample of 95 female and 89 male volunteers (with ages ranging from 18 to older than 60 years) exhibiting different pain pathologies, including headache, fever-dependent pain, joint pain, muscle aches, lower back pain, and menstrual cramps, was divided into two groups. The experimental group received 1 capsule/day containing either 200 mg or 400 mg of MyrLiq (corresponding to 8 mg and 16 mg of bioactive furanodienes, resp.) for 20 days, and the placebo group was given the same number of capsules with no MyrLiq. A score was recorded for all volunteers based on their previous experience with prescribed analgesics. For the male volunteers, pain alleviation was obtained with 400 mg of MyrLiq/day for almost all pathologies, whereas, for female volunteers, alleviation of lower back pain and fever-dependent pain was observed with only 200 mg of MyrLiq/day. These results indicate that MyrLiq has significant analgesic properties.